THE IMPACT OF JOB SATISFACTION ON TURNOVER INTENTION IN HOSPITAL EMPLOYEES: A CASE STUDY IN HOSPITAL X - DIAH PRASETYAWATI; ANDIK MATULESSY; AMANDA PASCA RINI (CV KULTURA DIGITAL MEDIA, 2024)
This study aims to investigate the relationship between job satisfaction and turnover intention among employees at private hospitals classified as Type B in Kabupaten X. The background of this research is based on the importance of understanding the factors that influence organizational dynamics in the healthcare sector, particularly in the context of hospitals. This study is expected to provide deeper insights into how job satisfaction affects employees' intentions to leave the organization. Additionally, it aims to offer valuable input to hospital management for designing policies and interventions that enhance employee well-being and strengthen organizational stability in facing existing challenges. The research findings indicate a significant correlation between job satisfaction with the turnover intention of contract employees at private hospitals in Kabupaten X. The hypothesis (H1) states that job satisfaction is negatively and significantly correlated with turnover intention. This research provides an important contribution to understanding the factors that influence turnover intention in the healthcare sector and offers practical recommendations for hospital management to improve job satisfaction to reduce employee turnover intention.